A method for preparing molybdenum oxide quantum dots
By forming nanomicelles through the self-assembly of molybdenum-based metal oxoacid salts and surfactant F68, combined with carbonization and calcination treatment, the problems of complexity and low yield in the synthesis of molybdenum oxide quantum dots were solved, enabling simple and efficient large-scale production.
Patent Information
- Application Number
- CN202411419810.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-12
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-10-12
AI Technical Summary
Existing methods for synthesizing molybdenum oxide quantum dots are complex and difficult to control, resulting in low quantum dot yields that are hard to meet the demands of large-scale production.
Molybdenum oxide quantum dots were obtained by self-assembling molybdenum-based metal oxometalates with surfactant F68 to form nanomicelles, followed by carbonization and calcination.
A simple and efficient preparation method is provided, which reduces costs, is suitable for large-scale production, and maintains the excellent performance of molybdenum oxide quantum dots.
Smart Images

Figure CN118954596B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of quantum dot nanomaterials, and specifically relates to a method for preparing molybdenum oxide quantum dots. Background Art
[0002] With the rapid development of nanotechnology, nanomaterials have shown great application potential in many fields. As a new type of nanomaterial, molybdenum oxide quantum dots are widely used in optoelectronic devices, photocatalysis, electrochemical catalysis, bioimaging, biomarkers and sensors due to their unique physical and chemical properties, such as excellent photoelectric properties, catalytic activity, fluorescence properties, good chemical stability and biocompatibility.
[0003] At present, the main method for synthesizing molybdenum oxide quantum dots is solvent thermal synthesis, but both methods have certain limitations. The solvent thermal synthesis process is complicated, difficult to control, and the quantum dot yield is low, which is not conducive to large-scale production. At present, there is a lack of a simple, efficient, low-consumption method that can stably prepare molybdenum oxide quantum dots with excellent performance, which is difficult to meet the growing application needs. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing molybdenum oxide quantum dots in view of the shortcomings of the prior art.
[0005] To achieve the above object, the present invention adopts the following technical solution:
[0006] The present invention provides a method for preparing molybdenum oxide quantum dots, comprising the following steps:
[0007] S1, using molybdenum-based metal oxoate and surfactant F68 to self-assemble in an organic solvent to form nanoscale micelles;
[0008] S2, carbonizing the micelles obtained in step S1 in an inert atmosphere, wherein the molybdenum-based polyoxometalate is converted into molybdenum oxide, and F68 is carbonized to form a carbon layer;
[0009] S3. The carbonized product is calcined in an air atmosphere to burn off the carbon layer, and the obtained material is ultrasonically dispersed in water to obtain molybdenum oxide quantum dots.
[0010] Furthermore, in step S1, the molybdenum-based metal oxoate is any one of ammonium molybdate, phosphomolybdic acid and silicomolybdic acid.
[0011] Furthermore, in step S1, the mass ratio of surfactant F68 to molybdenum-based metal oxoate is 1:(4-8).
[0012] Furthermore, in step S1, the mass ratio of surfactant F68 to molybdenum-based metal oxoate is 1:(4-6).
[0013] Furthermore, in step S1, the mass ratio of surfactant F68 to molybdenum-based metal oxoate is 1:6.
[0014] Furthermore, in step S1, the organic solvent is tetrahydrofuran or diethyl ether.
[0015] Furthermore, in step S2, the inert atmosphere is nitrogen or argon.
[0016] Furthermore, in step S2, the carbonization temperature is 350-400° C., and the carbonization time is 2-2.5 h.
[0017] Furthermore, in step S3, the calcination temperature is 400-450° C., and the calcination time is 1-1.5 h.
[0018] Furthermore, in step S3, the calcination temperature is 400° C. and the calcination time is 1 hour.
[0019] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:
[0020] (1) The present invention provides a method for preparing molybdenum oxide quantum dots. Traditional methods are mostly wet chemical methods, which are generally synthesized in small quantities in an organic solvent with the cooperation of a surfactant and are costly. The present invention is a solid chemical method, in which a molybdenum-based polyoxometalate and a surfactant F68 are self-assembled and then prepared by two-step calcination, which is cost-effective.
[0021] (2) Traditional methods require precise control and are difficult to scale up. This method is easy to operate, highly controllable, and suitable for scale-up preparation. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 A transmission electron microscopy image of the self-assembled micelle prepared by the present invention;
[0023] Figure 2 This is a transmission electron microscope image of the carbonized material prepared by the present invention;
[0024] Figure 3 This is a transmission electron microscope image of the material after air calcination of the present invention;
[0025] Figure 4 This is a transmission electron microscope image of the quantum dots prepared by the present invention;
[0026] Figure 5 This is a transmission electron microscope image of the quantum dots prepared in Example 2;
[0027] Figure 6 This is a transmission electron microscope image of the quantum dots prepared in Example 3;
[0028] Figure 7This is a transmission electron microscope image of the quantum dots prepared in Example 4;
[0029] Figure 8 This is a transmission electron microscope image of the quantum dots prepared in Example 5;
[0030] Fig. 9 This is a transmission electron microscope image of the quantum dots prepared in Example 6;
[0031] Fig.10 This is a transmission electron microscope image of the quantum dots prepared in Example 7;
[0032] Fig.11 This is a transmission electron microscope image of the quantum dots prepared in Example 8;
[0033] Fig.12 This is a transmission electron microscope image of the quantum dots prepared in Example 9;
[0034] Fig.13 This is a transmission electron microscope image of the quantum dots prepared in Comparative Example 1;
[0035] Fig.14 This is a transmission electron microscope image of the quantum dots prepared in Comparative Example 2;
[0036] Fig.15 This is a transmission electron microscope image of the quantum dots prepared in Comparative Example 3;
[0037] Fig.16 This is a transmission electron microscope image of the quantum dots prepared in Comparative Example 4;
[0038] Fig.17 This is a transmission electron microscope image of the quantum dots prepared in Comparative Example 5;
[0039] Fig.18 This is a transmission electron microscopy image of the quantum dots prepared in Comparative Example 6;
[0040] Fig.19 This is a transmission electron microscope image of the quantum dots prepared in Comparative Example 7. DETAILED DESCRIPTION
[0041] In order to make the purpose, technical scheme and advantages of the present invention clearer, the specific embodiments of the present invention are further described in detail below in conjunction with specific examples and drawings. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this field or the product instructions are used. If the manufacturer of the reagents or instruments is not specified, they are all conventional products that can be obtained commercially.
[0042] The surfactants F68 and F127 used in the present invention are provided by Shanghai Titan Technology Co., Ltd. The chemical composition of the surfactants F68 and F127 is mainly a polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, and the molecular weights of the two are different.
[0043] Example 1
[0044] This embodiment provides a method for preparing molybdenum oxide quantum dots:
[0045] Weigh 1.0 g of F68 and dissolve it in 2 mL of tetrahydrofuran, weigh 6.0 g of phosphomolybdic acid and dissolve it in 2 mL of tetrahydrofuran, mix the two solutions quickly, and then dry them at 40-80°C. The dried sample is placed in a tube furnace, and the temperature is raised to 350°C at 1°C / min under N2 atmosphere, and carbonized for 2 h. After carbonization, the air atmosphere is introduced, and the temperature is raised to 400°C at 5°C / min, and further calcined for 1 h. The calcined material is placed in pure water, and molybdenum oxide quantum dots can be obtained by ultrasonic dispersion.
[0046] Example 2
[0047] This embodiment provides a method for preparing molybdenum oxide quantum dots:
[0048] The method is basically the same as Example 1, except that the molybdenum-based metal oxoate is molybdenum silicate.
[0049] Example 3
[0050] This embodiment provides a method for preparing molybdenum oxide quantum dots:
[0051] The method is basically the same as Example 1, except that the molybdenum-based metal oxoate is ammonium molybdate.
[0052] Example 4
[0053] The method is basically the same as Example 1, except that the mass ratio of surfactant F68 to molybdenum phosphate is 1:4.
[0054] Example 5
[0055] The method is basically the same as Example 1, except that the mass ratio of surfactant F68 to molybdenum phosphate is 1:8.
[0056] Example 6
[0057] The process is basically the same as Example 1, except that the organic solvent is ether.
[0058] Example 7
[0059] Basically the same as Example 1, except that the carbonization temperature is 400°C.
[0060] Example 8
[0061] The method is basically the same as Example 1, except that the air calcination temperature is 450°C.
[0062] Example 9
[0063] Basically the same as Example 1, except that the surfactant is F127.
[0064] Comparative Example 1
[0065] Basically the same as Example 1, except that F68 is not added.
[0066] Comparative Example 2
[0067] The method is basically the same as Example 1, except that the mass ratio of surfactant F68 to molybdenum phosphate is 1:9.
[0068] Comparative Example 3
[0069] The method is basically the same as Example 1, except that the mass ratio of surfactant F68 to molybdenum phosphate is 1:3.
[0070] Comparative Example 4
[0071] Basically the same as Example 1, except that the carbonization temperature is 450°C.
[0072] Comparative Example 5
[0073] Basically the same as Example 1, except that the carbonization temperature is 250°C.
[0074] Comparative Example 6
[0075] Basically the same as Example 1, except that the air calcination temperature is 500°C.
[0076] Comparative Example 7
[0077] Basically the same as Example 1, except that the air calcination temperature is 300°C.
[0078] Performance characterization:
[0079] (1) Transmission electron microscopy (TEM) observation
[0080] Figure 1 This is a transmission electron microscopy image of the self-assembled micelles prepared in the present invention. It can be seen from the image that the size of the micelles is about 5nm;
[0081] Figure 2 This is a transmission electron microscopy image of the carbonized material prepared in the present invention. It can be seen that the clusters of molybdenum oxide are evenly distributed in the carbon skeleton;
[0082] Figure 3 This is a transmission electron microscope image of the material after air calcination of the present invention. It can be seen that after air calcination, the material is composed of molybdenum oxide clusters;
[0083] Figure 4This is a transmission electron microscope image of the quantum dots prepared by the present invention. After the material is calcined in air and subjected to ultrasound, molybdenum oxide is peeled off from the material in the form of quantum dots;
[0084] Figure 5 This is a transmission electron microscope image of the quantum dots prepared in Example 2. The size of the quantum dots is about 6 nm.
[0085] Figure 6 This is a transmission electron microscope image of the quantum dots prepared in Example 3, and the size of the quantum dots is about 8 nm;
[0086] Figure 7 This is a transmission electron microscope image of quantum dots prepared in Example 4. It can be seen that the mass ratio of surfactant F68 to molybdenum phosphate is 1:4, and the prepared sample generates quantum dots;
[0087] Figure 8 This is a transmission electron microscopy image of quantum dots prepared in Example 5. It can be seen that the mass ratio of surfactant F68 to molybdenum phosphate is 1:8, and the prepared sample generates quantum dots;
[0088] Fig. 9 This is a transmission electron microscopy image of the quantum dots prepared in Example 6. It can be seen that changing the organic solvent does not affect the formation of quantum dots;
[0089] Fig.10 This is a transmission electron microscope image of quantum dots prepared in Example 7. It can be seen that changing the carbonization temperature within a certain range does not affect the formation of quantum dots;
[0090] Fig.11 This is a transmission electron microscope image of quantum dots prepared in Example 8. It can be seen that changing the air calcination temperature within a certain range does not affect the formation of quantum dots;
[0091] Fig.12 This is a transmission electron microscopy image of quantum dots prepared in Example 9. It can be seen that replacing with a similar surfactant does not affect the formation of quantum dots;
[0092] Fig.13 This is a transmission electron microscopy image of quantum dots prepared in Comparative Example 1; it can be seen that without adding a surfactant, self-assembled micelles cannot be formed and quantum dots cannot be further generated;
[0093] Fig.14 This is a transmission electron microscopy image of quantum dots prepared in Comparative Example 2; it can be seen that the mass ratio of surfactant F68 to molybdenum phosphate is 1:9, the self-assembled micelles are too large, and quantum dots cannot be generated;
[0094] Fig.15 This is a transmission electron microscopy image of quantum dots prepared in Comparative Example 3; it can be seen that the mass ratio of surfactant F68 to molybdenum phosphate is 1:3, the self-assembled micelles are too small, and quantum dots cannot be generated;
[0095] Fig.16 This is a transmission electron microscope image of quantum dots prepared in Comparative Example 4; it can be seen from the figure that quantum dots cannot be obtained when the calcination temperature is 450°C, because molybdenum oxide will be sintered at a higher calcination temperature;
[0096] Fig.17 This is a transmission electron microscope image of quantum dots prepared in Comparative Example 5; it can be seen from the figure that quantum dots cannot be obtained when the calcination temperature is 250°C, because the carbon skeleton cannot be formed at a lower calcination temperature;
[0097] Fig.18 This is a transmission electron microscope image of the quantum dots prepared in Comparative Example 6. As can be seen from the figure, quantum dots cannot be obtained when the calcination temperature is 500°C, because molybdenum oxide will be sintered at a higher calcination temperature;
[0098] Fig.19 This is a transmission electron microscopy image of the quantum dots prepared in Comparative Example 7. As can be seen from the image, quantum dots cannot be obtained when the calcination temperature is 300°C, because the carbon skeleton cannot be removed at a lower calcination temperature.
[0099] (2) Quantum dot yield analysis
[0100] The yields of quantum dots prepared in Examples 1-9 were statistically analyzed, and the results are shown in Table 1.
[0101] Quantum dot yield = mass of quantum dots obtained / added molybdenum oxide equivalent
[0102] Table 1. Summary of quantum dot yields of the examples.
[0103]
[0104] It can be seen that the yield of quantum dots prepared by this method is approximately between 25% and 30%, and the loss mainly comes from mechanical losses in processes such as calcination and centrifugation.
[0105] (3) Analysis of quantum dot application performance
[0106] 30 mg of quantum dots were loaded on graphene to generate H2O2 in situ. The H2O2 production of Example 1 within 3 hours was 187.5 µmol / g, and the graphene without quantum dots was used as a blank control group, and the H2O2 production was 7.5 µmol / g. Taking Example 1 as a reference, the H2O2 production of other examples and comparative examples is shown in Tables 1 and 2.
[0107] Table 2. H2O2 production results of the examples.
[0108]
[0109] Table 3. H2O2 production results of comparative examples.
[0110]
[0111] The experimental results show that the quantum dots in the embodiment have a higher H2O2 yield; the quantum dots are not formed in the comparative example, and there is no quantum effect, resulting in a lower H2O2 yield. The H2O2 yields of other comparative examples and blank controls are relatively small, indicating that the Mo element is the main active substance.
[0112] In the absence of conflict, the above embodiments and features in the embodiments may be combined with each other.
[0113] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing molybdenum oxide quantum dots, characterized in that: The following steps are involved: S1. Self-assembly of a molybdenum-based metal oxoate and a surfactant F68 in an organic solvent to form nanoscale micelles; the molybdenum-based metal oxoate is any one of ammonium molybdate, phosphomolybdic acid and silicomolybdic acid; the mass ratio of the surfactant F68 to the molybdenum-based metal oxoate is 1:(4-8); S2, carbonizing the micelles obtained in step S1 in an inert atmosphere, wherein the molybdenum-based polyoxometalate is converted into molybdenum oxide, and F68 is carbonized to form a carbon layer; the carbonization temperature is 350-400° C., and the carbonization time is 2-2.5 h; S3, calcining the carbonized product in an air atmosphere to burn off the carbon layer, and dispersing the obtained material in water by ultrasonic to obtain molybdenum oxide quantum dots; The calcination temperature is 400-450° C., and the calcination time is 1-1.5 hours.
2. The preparation method according to claim 1, characterized in that In step S1, the organic solvent is tetrahydrofuran or diethyl ether.
3. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of surfactant F68 to molybdenum-based metal oxoate is 1:(4-6).
4. The preparation method according to claim 2, characterized in that: In step S1, the mass ratio of surfactant F68 to molybdenum-based metal oxoate is 1:
6.
5. The preparation method according to claim 1, characterized in that: In step S2, the inert atmosphere is nitrogen or argon.
6. The preparation method according to any one of claims 1 to 5, characterized in that: In step S3, the calcination temperature is 400° C. and the calcination time is 1 hour.
7. The preparation method according to any one of claims 1 to 5, characterized in that: The yield of preparing molybdenum oxide quantum dots is between 25% and 30%.
8. Molybdenum oxide quantum dots prepared by the preparation method according to any one of claims 1 to 5.
9. Use of the molybdenum oxide quantum dots as claimed in claim 7 in the preparation of H2O2.
10. A method for preparing H2O2, characterized in that: The molybdenum oxide quantum dots prepared by the preparation method according to any one of claims 1 to 5 are loaded on graphene to generate H2O2 in situ.
Citation Information
Patent Citations
Metal oxide ordered crossed nanowire array and preparation method thereof
CN110127620A